Awards are career catalysts for young talents in highly competitive job markets - Florian Bünning; Ben Chan; Sascha Leonard Schmidt; Dominik Schreyer; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2021)
Despite the potential importance of awards as a possible career catalyst, the theoretical and empirical research on awards is still in its infancy. Here, we address this notable shortcoming in the economic literature by exploring data from German youth football. Analyzing whether an early career award, the so-called Fritz Walter Medal, significantly affects the awardee's career trajectory in a highly competitive environment, where performance differences are often hardly perceivable, we find that receiving an early career award seems, per se, to be a robust positive signal for a player's future career success. Intriguingly, though, both the award characteristics, that is, whether it is bestowed in gold, silver, or bronze, and also the exact age at which the awardee receives the bestowal only add limited explanatory power.
Keywords: A13; M52; J30; Z20; 330; Awards; career effects; football/soccer; incentives; personnel economics; signaling theory